Pengaruh Ukuran Perusahaan, Free Cash Flow, Growth, Leverage, Dan Likuiditas Terhadap Dividend Payout Ratio Pada Perusahaan Real Estate And Property Yang Terdaftar Di Bei Tahun 2011-2014 - Sasongko, Arief Budi; , Dr. Fatchan Achyani, SE, M.Si (2017)
This research aimed to analyze the influence of Size Company (SIZE), Free Cash Flow, Growth, Leverage (DER), and Liquidity (CR) to Dividend Payout Ratio (DPR) in real estate and property companies which listed in Indonesian Stock Exchange (IDX) from 2011 to 2014. The research sample consisted of 8 companies of 50 real estate and property companies listed on IDX by the observation numbers of 31 observational data. The sampling method was done by using purposive sampling. The researched data was obtained from ICMD and IDX. The data analysis technique used in this research is multiple linear regression. Hypothesis testing using t statistics used in this research to test the partial regression coefficients as well as f-statistics to test the significance of the influence together, with the level of significance of 5%. Other than that, all the variables had been tested with the Normality test, Multicollinearity test, Autocorrelation test, and Heteroskidastity test. The results showed that all variables passed the classical assumption test and suitable to be used as research data. T-test statistical on Dividend Payout Ratio (DPR) indicated that only Leverage (DER) has significant influence on Dividend Payout Ratio (DPR) whereas Size Company (Size), Free Cash Flow, Growth, and Liquidity (CR) has no significant influence on Dividend Payout Ratio (DPR).